2020
DOI: 10.3390/toxins12020128
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Efficacy of OnabotulinumtoxinA, Sacral Neuromodulation, and Peripheral Tibial Nerve Stimulation as Third Line Treatment for the Management of Overactive Bladder Symptoms in Adults: Systematic Review and Network Meta-Analysis

Abstract: The American Urological Association guidelines for the management of non-neurogenic overactive bladder (OAB) recommend the use of OnabotulinumtoxinA, sacral neuromodulation (SNM), and peripheral tibial nerve stimulation (PTNS) as third line treatment options with no treatment hierarchy. The current study used network meta-analysis to compare the efficacy of these three modalities for managing adult OAB syndrome. We performed systematic literature searches of several databases from January 1995 to September 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 35 publications
0
26
0
1
Order By: Relevance
“…The indications include detrusor underactivity, neurogenic detrusor sphincter dyssynergia, and non-neurogenic DV. Although most studies demonstrated the efficacy of this treatment in voiding dysfunction caused by urethral sphincter hyperactivity of different etiologies, the subjective improvement rate after BoNT-A urethral sphincter injection was only 60% [ 13 , 14 , 19 ]. In the experience of the authors for the present study, patients who have an open BN on voiding cystourethrography have predictably successful therapeutic results [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The indications include detrusor underactivity, neurogenic detrusor sphincter dyssynergia, and non-neurogenic DV. Although most studies demonstrated the efficacy of this treatment in voiding dysfunction caused by urethral sphincter hyperactivity of different etiologies, the subjective improvement rate after BoNT-A urethral sphincter injection was only 60% [ 13 , 14 , 19 ]. In the experience of the authors for the present study, patients who have an open BN on voiding cystourethrography have predictably successful therapeutic results [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many treatment modalities have been used to relax the urethral sphincter and pelvic floor muscles, including pelvic floor muscle training, antimuscarinic therapy, sacral nerve neuromodulation, and posterior tibial nerve stimulation [ 5 , 11 , 12 ]. Since no definitive medical treatment is currently available for DV, clinicians have enthusiastically used urethral botulinum toxin A (BoNT-A) for this off-label indication [ 13 ]. However, a satisfactory treatment outcome with BoNT-A has not been achievable for all patients with DV [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of neurotransmitters and neural pathways are participated in the control of bladder urine storage and subsequent emptying, and undermine these neurotransmitters and neural pathways may cause the dysfunction of vesical. Generally, OAB is considered to be caused by the vesical detrusor muscle' overactivity, resulting in the suddenly contracting of vesical, although the vesical is not filled 22 . Vibegron is a new β3‐adrenergic receptor agonist.…”
Section: Discussionmentioning
confidence: 99%
“…Approved third‐line treatment options for OAB include onabotulinumtoxinA, peripheral tibial nerve stimulation (PTNS), and sacral nerve stimulation (SNS) 75 . Each option demonstrates significant benefit in controlling urinary symptoms versus placebo/sham treatment 76 . Patients should be carefully monitored and counseled appropriately based on the advantages and disadvantages of the individual treatments.…”
Section: Treatmentmentioning
confidence: 99%